Children from migrant backgrounds: Who are their Kita peers? - Ludovica Gambaro (DIW Economic Bulletin, 2017)
In Germany, attendance in early childhood education and care (ECEC) centers has soared in the last twenty years, making them a key context in which children learn. For children from migrant backgrounds who speak a foreign language at home, participation in ECEC has the potential of providing them with early German language exposure. One important but often overlooked factor in this respect is the composition of a child's peer group. Do children from migrant backgrounds attend ECEC centers where the majority of their peers are also from migrant backgrounds? This report offers the first systematic evidence for Germany of how children, and children from migrant backgrounds in particular, are distributed across ECEC centers, thus assessing the level of segregation. Using administrative data from 2007 to 2016, it shows that one-third of children who mainly speak a foreign language at home attend centers where the majority of their peers have a similar background. The report argues that peer group composition is a crucial aspect affecting the quality of children's experiences in ECEC. Luckily, it is also an aspect that can be influenced by careful policy design.
Keywords: J15; J13; I24; H75; 330; early education and care; peer composition; segregation; migrant background